Neuroprotective Effect of Colocasia esculenta Var. Mentawai Corm Flour High-Fat Diet Fed Mice - Ramadhan Marviano, Fajri; Santoso, Putra; Rahayu, Resti (Journal of Cellular Neuroscience and Oxidative Stress, 2024)
The transformation of our era, resulting in a change in dietary habits towards a higher intake of fatty foods, presents a worldwide health issue. Among these challenges is neurodegeneration, which leads to cognitive impairment. It is imperative to seek alternative solutions rooted in nature to address the limitations associated with non-natural treatment methods. This entails harnessing the properties of secondary metabolite compounds found in plants, such as Colocasia esculenta Var. Mentawai. This research aims to assess the efficacy of C. esculenta Var. Mentawai corm as neuroprotective agents in mitigating CNS damage and preventing cognitive decline associated with neurodegeneration. Daily administration of a high-fat diet and a mixture of taro flour is conducted on young adult male mice for a duration of 60 days. Furthermore, analysis of the neurocognitive ability of mice, determination of malondialdehyde levels, and observation of histopathological structures on brain tissue were carried out. The results showed that the group of mice fed with taro flour mixture effectively showed a positive impact on maintaining neurocognitive abilities and histopathological structure of brain tissue against neurodegeneration (p
Keywords: Medical Physiology (Other); Biochemistry and Cell Biology (Other); Sinirbilim (Diğer); Biyokimya ve Hücre Biyolojisi (Diğer); high fat diet; neurodegeneration; obesity; secondary metabolites; taro.; Hayvan Fizyolojisi - Hücre; Pharmacology and Pharmaceutical Sciences (Other); Tıbbi Fizyoloji (Diğer); Animal Physiology - Cell; Eczacılık ve İlaç Bilimleri (Diğer); Neurosciences (Other); 3. Good health